Wing Design Optimization for a Long-Endurance UAV using FSI Analysis and the Kriging Method - Son, Seok-Ho; Choi, Byung-Lyul; Jin, Won-Jin; Lee, Yung-Gyo; Kim, Cheol-Wan; Choi, Dong-Hoon (International journal of aeronautical and space sciences, 2016)
In this study, wing design optimization for long-endurance unmanned aerial vehicles (UAVs) is investigated. The fluidstructure integration (FSI) analysis is carried out to simulate the aeroelastic characteristics of a high-aspect ratio wing for a long-endurance UAV. High-fidelity computational codes, FLUENT and DIAMOND/IPSAP, are employed for the loose coupling FSI optimization. In addition, this optimization procedure is improved by adopting the design of experiment (DOE) and Kriging model. A design optimization tool, PIAnO, integrates with an in-house codes, CAE simulation and an optimization process for generating the wing geometry/computational mesh, transferring information, and finding the optimum solution. The goal of this optimization is to find the best high-aspect ratio wing shape that generates minimum drag at a cruise condition of CL = 1.0. The result shows that the optimal wing shape produced 5.95 % less drag compared to the initial wing shape. KCI Citation Count: 3